“Should we vote for women just because they are women?” : intersectional assessment of women’s political participation in Zambia - Kinnunen, Lotta (2020)
The aim of this study was to define and assess the themes for women’s political participation in Zambia in the framework of feminist theory. As the research went on, the central theoretical concepts were narrowed down to anti-essentialism and feminist intersectionality. The use of strategic essentialism by harnessing the stereotypical notions of women’s roles and their innate good qualities for the wider good is quite common. It is used by women’s organisations in Zambia, internationally, and also in UN agencies working towards gender equality. However, using essentialist notions of gender in advocacy work can be risky because it might result in re- enforcing the already existing notions and stereotypes, and the potential political transformative power goes to waste and no change occurs. The primary data consists of ten (10) semi-structured interviews, conducted in the Southern Province of Zambia in December 2006, three months after the Zambian tri-partite elections, and during my internship with Women for Change (WfC), a Zambian women’s organisation. The secondary data collected and used were advocacy materials developed and used by WfC for the pre-electoral campaign “Vote for Women!”, my field notes and four (4) semi-structured interviews with the key people of the Zambian Women’s Movement, and co-coordinators of the electoral campaign. The data was analysed using thematic analysis; within the theoretical framework of anti-essentialism and intersectionality. The findings of my research indicate that the use of strategic feminism quickly becomes counterproductive, and starts feeding back into the stereotypes, therefore having no transformative power. On the other hand, my study shows the importance of intersectionality for a more diverse and nuanced picture of the intersections of social divisions which in this study were identified as gender/ethnicity and gender/class. Through these intersections, the structures of patriarchy and inequality become visible.